Pengaruh Penempatan Kerja dan Gaya Kepemimpinan terhadap Kinerja Pegawai dengan Disiplin Kerja sebagai Variabel Intervening pada Kantor Camat Pemulutan Kabupaten Ogan Ilir - Hasyim, Nasrullah (LPPM Universitas Multi Data Palembang, 2024)
Abstract: This study aims to determine the Effect of Job Placement and Leadership Style on Work Discipline and the Impact on the Performance of Employees of the Pemulutan Subdistrict Office of Ogan Ilir Regency. The research method used was quantitative and used path analysis with the Smart PLS 3.3.3 statistical application, and a sample of 40 respondents. The results of this study show that there is a positive and significant influence of job placement and leadership style on work discipline (t-statistic ≥ 1.96 and p-value ≤ 0.05), there is a positive and significant influence of job placement and leadership style on employee performance (t-statistic ≥ 1.96 and pvalue ≤ 0.05) and there is a positive and significant influence of work discipline on employee performance (tstatistic ≥ 1.96 and p-value ≤ 0.05).Keywords: Job Placement, Leadership Style, Work Discipline, Employee Performance